2008
DOI: 10.1142/s0217979208050553
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Deformation Behavior of High Strength Steel Sheet Under Non-Proportional Loading and Its Modeling

Abstract: This paper deals with plastic deformations of a high tensile strength steel sheet (HTSS sheet) under biaxial stress condition including strain path. Using a cruciform specimen of a HTSS sheet of 780MPa-TS, experiments under proportional and non-proportional loadings were investigated. Numerical simulations of stress-strain responses for several strain paths after biaxial stretching were conducted using a large-strain cyclic plasticity model (Yoshida-Uemori model). The results of numerical simulation agrees wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It is found the experimental data of cross effect show very complicated stress–strain responses . While the stress–strain responses in both 45° and 90° direction with 5% plastic pre‐strain do not show the yield plateau after re‐yielding, the stress–strain responses in the two directions with 10% plastic pre‐strain shows the yield plateau after stress‐reversal.…”
Section: Resultsmentioning
confidence: 93%
“…It is found the experimental data of cross effect show very complicated stress–strain responses . While the stress–strain responses in both 45° and 90° direction with 5% plastic pre‐strain do not show the yield plateau after re‐yielding, the stress–strain responses in the two directions with 10% plastic pre‐strain shows the yield plateau after stress‐reversal.…”
Section: Resultsmentioning
confidence: 93%
“…An appropriate choice of the combination of constitutive model is of vital important for an accurate sheet-metal stamping simulation [1][2][3] For that purpose, "Yoshida-Uemori model" has been proposed and its high capability in simulating cyclic behavior. The model has been already verified by comparing the numerical simulations with several evidences [4][5][6][7]. However, it was found that the verification of this model, especially the details of the non-proportional deformation behaviors, is not guaranteed for low yield point materials.…”
Section: Introductionmentioning
confidence: 99%